CONSUMER PURCHASE INTENTION OF SECOND-HAND SMARTPHONE: MODERATING ROLE OF SUBJECTIVE NORMS AND KNOWLEDGE - Edy Purwanto Edy (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
This study aims to determine the effect of attitude toward behavior on purchase intention and to determine the role of subjective norm and consumer knowledge in moderating the effect of Attitude toward consumer purchase intentions. The object in this study is focused on the second hand smartphone. The sample size used was 200 respondents. Determination of the sample using a purposive sampling technique. Data obtained through distributing questionnaires. Hypothesis testing is performed using simple linear regression analysis and moderated regression analysis (MRA). The results of this study indicate that the attitude toward behavior has an effect on purchase intention. Subjective norm and knowledge variables moderate the effect of attitude toward behavior on purchase intention. It is hoped that this research can add insight into the theory of reasoned action (TRA) in predicting consumer purchase intentions on second hand smartphone. This research is also useful for smartphone business actor in understanding the factors that influence consumer purchase intentions. This study has limitations, namely: this research was only conducted in one district, namely Sumenep Regency. in the future research can be carried out in several cities in Indonesia. This study only uses one object, namely the second hand smartphone, so future research needs to use a different product category.